Pengaruh Marketing Mix Terhadap Kepuasan Nasabah Produk Funding Pada Bank Syariah Indonesia Cikarang - Hamidah, Innaroh; Isnandar, Fajri Ryan (LPPM Universitas Islam 45, 2024)
Marketing mix or marketing mix plays an important and potential role for the success of a company in today's business world. Therefore, to face competition that grows in line with the development of science and technology, one must prepare various preparations of appropriate and measurable marketing strategies for the continuity of a company so that it can make a greater contribution to the company. This study aims to examine the effect of product, price, place, promotion on customer satisfaction at Bank Syariah Indonesia KCP Cikarang, the sample used in this study was a purposive sample, the sample in this study was 100 respondents, the data collection technique used was a questionnaire. This questionnaire will be tested with several tests, namely multiple linear regression, normality test, heteroscedasticity test, and multicollinearity test, and hypothesis testing includes R test, F test, and T test using SPSS 26.0. The test results of this study are the product has a significant positive effect on customer satisfaction, price has a significant positive effect on customer satisfaction, place has a significant positive effect on customer satisfaction, promotion has an insignificant positive effect on customer satisfaction, product, price, place, promotion has an influence on customer satisfaction. customer.